The Smarter Power Strip - Design and implementation of a smart power strip - Baxemyr, Marco; Broberg, Johannes; Henriksson, Mattias; Swetzén, Johan (My University, 2014)
It is estimated that up to 20% of U.S. households' power consumption is used by standby equipment (Ross and Meier 2000). In this report, we describe the design and implementation of a smart power strip, with the purpose of lowering such useless energy waste. The device puts its users in control of their consumption by providing monitoring of the power drawn by appliances connected to it, and the ability to remotely turn these appliances on and o . Power consumption history and control can be accessed by users through a web application, and the power strip communicates with this web application over the Internet via an embedded wireless interface. Furthermore, through the open design of the device it is easy for third parties to create services that utilize it. A set of desired features are speci ed, and a prototype is developed accordingly. To evaluate the prototype empirical tests are performed and results indicate that, with some further development of the software, its goals would be achieved. This opens up for the device to be used as a tool in the important task of lowering power consumption in today's society.
Keywords: Data- och informationsvetenskap; Computer and Information Science